Sosialisasi Pelayanan Perpustakaan Sebagai Media Komunikasi dan Informasi di Perguruan Islam Al-Ulum Terpadu Medan - Amin, Afriadi; Amru Yasir; Budiman Purba (Unity Academy, 2023)
Nowadays, libraries are rarely visited by people or students due to the widespread use of sophisticated equipment to search for information, but there are still some people who come to the library to look for important references, but most people who come to the library are often uncomfortable because of the service. from admin and library which is less than satisfactory. The library at the Medan Integrated Al-Ulum Islamic College still has a manual concept and is still rigid in the services provided to library visitors. The Community Service Team is here to provide socialization regarding service to visitors who come in a good and friendly manner, and with this community service it teaches officers to be able to communicate and provide good service in the future, because the library is a facility that provides information for the general public. Keywords: Information, Communication, Services, Library, Community Service.